2016
DOI: 10.1007/s12026-015-8782-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA-G +3142 C>G polymorphism and breast cancer in Tunisian population

Abstract: HLA-G is highly expressed in cancer. Also, it is associated to its progression. Here, we explored the relationship between two HLA-G polymorphisms with breast cancer (BC) and tried to make a correlation with sHLA-G levels. We genotyped 104 patients with BC and 83 controls (CTRL) for HLA-G 14-bp insertion/deletion (Ins/Del) and HLA-G +3142 C>G polymorphisms. The mutations were identified with PCR and PCR-RFLP. The sHLA-G dosage was performed on plasma samples by a specific ELISA. A significant association with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Interestingly, the wild-type ins/ins genotype was absent among Saudi patients, suggesting that the ins allele has a highly protective effect. However, in other studies, no associations were found in a group of women from northern Tunisia (Zidi et al, 2016). This was also observed in a South Korean population (Jeong et al, 2014) and Azeri population located in northwestern Iran (Haghi et al, 2015).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Interestingly, the wild-type ins/ins genotype was absent among Saudi patients, suggesting that the ins allele has a highly protective effect. However, in other studies, no associations were found in a group of women from northern Tunisia (Zidi et al, 2016). This was also observed in a South Korean population (Jeong et al, 2014) and Azeri population located in northwestern Iran (Haghi et al, 2015).…”
Section: Discussionmentioning
confidence: 74%
“…Different results have also been reported regarding the association between the level of expression of HLA-G molecule and BC. While the majority of these studies have reported increased levels of HLA-G in patients (Chen et al, 2010;Eskandari-Nasab et al, 2013;Jeong et al, 2014;Ramos et al, 2014;Zidi et al, 2016), a few studies, however, did not find differences between patients and controls (Palmisano et al, 2002). A recent meta-analysis revealed that the HLA-G 14-bp ins/del polymorphism may contribute to BC susceptibility and overall cancer risk in Asian populations (Ge et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The meta-analysis study on cancer risk reported significant association of 14-bp Ins/Del polymorphism with breast cancer 29. In the Tunisian population,30 there is no association of 14-bp Ins/Del polymorphism with breast cancer. Though the 14-bp Ins/Del polymorphism is not associated with breast cancer predisposition in Brazilian31 and Iranian-Azeri32 populations, it has been shown to contribute to shorter survival time and disease progression, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Articles included comprised case-control studies involving the HLA-G 3′UTR 14-bp polymorphism and clinical situations/ diseases. Studies were grouped according to clinical characteristics, pathogenesis and immune response as follow: (1) cancer 2 -B-Cell Lymphoma [27], Breast Cancer [28][29][30][31][32], Cervical Cancer [33][34][35][36], Colorectal cancer [37], Esophageal Cancer [38], Hepatocellular Carcinoma [39][40][41], Head and Neck Squamous-Cell Carcinoma (HNSCC) [42], Lung Cancer [43], Neuroblastoma [44], Papillary Thyroid Cancer [45] and Prostate Cancer [46]; (2) autoimmune diseases 3 -Hashimoto's Thyroiditis [45], Juvenile Idiopathic Arthritis [47], Multiple Sclerosis [48][49][50][51], Non-segmental Vitiligo [52], Pemphigus Vulgaris [53], Rheumatoid Arthritis [47,[54][55][56][57][58], Systemic Lupus Erythematosus (LES) [59][60][61][62][63][64][65][66][67] and Type 1 Diabetes [68]…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%